Synthesis of polyethylene-g-polydimethylsiloxane graft copolymers by copolymerization of ethylene with polydimethylsiloxane macromonomer. (September 2019) - Tian, Baozheng; Zhang, Xianwei; Fan, Hong
Graphical abstract: Highlights: A novel octene-terminated PDMS macromonomer is synthesized with good yield. The first study on the efficient preparation of PE-g-PDMS by direct copolymerization. The effect of PDMS content on copolymer microstructure is studied. Small addition of PE-g-PDMS into HDPE can improve the melting flow property. Abstract: This paper discusses the synthesis of polyethylene-g-polydimethylsiloxane (PE-g-PDMS) graft copolymers through a facile macromonomer approach. A novel octene-terminated PDMS macromonomer was synthesized via anionic ring-opening polymerization of hexamethylcyclortrisiloxane and the subsequent chain-end capping with dimethyl(oct-7-enyl)chlorosilane. A systematic investigation was conducted on the VCl3 (THF)3 /Et2 AlCl-catalyzed copolymerizations of the PDMS macromonomer with ethylene by varying the macromonomer feed. The relatively high activity of 11.6 kg/(mmolV ·h) was observed even at a rather high macromonomer feed of 160 mmol/L, which is first reported and of great significance in the efficient fabrication of polyethylene-g-polysiloxane graft copolymers. The resulting PE-g-PDMS copolymers were characterized to determine the chain structure, molecular weight and molecular weight distribution. The highest macromonomer incorporation (3.77 mol%) was achieved at the highest macromonomer feed with a decreased molecular weight and a narrower molecular weight distribution. DSC analysis revealed that melting temperature and crystallinity of PE-g-PDMS copolymers systematically decreased with increasing of the PDMS macromonomer incorporation. When quite a small amount (2 wt%) of PE-g-PDMS copolymers was added to HDPE via melt blending, the melt flow rate of HDPE increased by 32% and the mechanical properties remained almost unchanged.